2015
DOI: 10.1002/jbio.201500109
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy as a diagnostic tool for monitoring acute nephritis

Abstract: Both acute nephritis and chronic nephritis account for substantial morbidity and mortality worldwide, partly due to the lack of reliable tools for detecting disease early and monitoring its progression non-invasively. In this work, Raman spectroscopy coupled with multivariate analysis are employed for the first time to study the accelerated progression of nephritis in anti-GBM mouse model. Preliminary results show up to 98% discriminant accuracy for the severe and midly diseased and the healthy among two strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…However, Raman spectroscopy was never used before to study metabolomics in FSGS. Li et al demonstrated that Raman spectroscopy combined with multivariate analysis can be a potential non-invasive diagnostic tool for nephritis in an anti-GBM mouse model 47 . We previously used Raman to detect cell stress induced by micro particles 48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Raman spectroscopy was never used before to study metabolomics in FSGS. Li et al demonstrated that Raman spectroscopy combined with multivariate analysis can be a potential non-invasive diagnostic tool for nephritis in an anti-GBM mouse model 47 . We previously used Raman to detect cell stress induced by micro particles 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Dominant Raman peak is at 1620 cm −1 , which corresponds to the ring stretching mode of porphyrin. Tentative Raman band assignments are shown in Table . Because the urine samples were stored at −80 °C and thawed before SERS measurements, the impact of freeze and thaw cycle on SERS spectra was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Some distinctive spike features are observed in the difference spectrum which implies the difference in the SERS spectra. More sophisticated statistical techniques, e.g., hierarchical cluster analysis (HCA) and/or discriminant analysis (DA) can be employed to obtain quantitative bacterial identification/classification [ 46 , 47 , 48 ]. Reproducibility has been an issue for the widespread adoption of SERS-based bacteria identification since the enhancement phenomenon depends on the microscopic morphology and stability of the SERS substrate.…”
Section: Resultsmentioning
confidence: 99%